Differences in the count of blood cells pre-and post-chemotherapy in patients with cancer: a retrospective study (2022) - Kassie, Tadele Derbew; Yimenu, Bayu Wondimneh; Baye Temesgen, Gelagey; Shimelash, Rahel Asres; Abneh, Aysheshim Asnake (Frontiers in Medicine, 2025)
IntroductionCancer is a disease characterized by uncontrolled cell growth that can invade and spread to other body parts. Drugs used for chemotherapy can cause damage to non-cancer cells and lead to a low blood cell count. There are controversial findings regarding the differences in the counts of blood cell types. Studies on the counts of blood cell types before and after chemotherapy are limited. Therefore, this study aimed to address this gap.MethodsA retrospective study was conducted on 354 patients from 1 September 2022 to 1 October 2022 to compare blood cell type profiles in pre-and post-operative periods. A chi-squared test and paired t-test were performed to analyze the data.ResultsData were collected from 354 patients. The mean age of the respondents was 41.26 (±16.67) years. At the initial diagnosis, 167 patients (47%) were categorized as having stage III cancer, while 159 patients were categorized as having stage IV cancer. Before and after chemotherapy the mean heamoglobin level is 12.95 g/dL and 12.30 g/ dL respectively and the prevalence of anemia among cancer patients before chemotherapy and after chemotherapy was 25.14% (95%:20.88, 29.94) and 35.54% (95%: 30.75; 40.73), respectively. The mean value of neutrophils before and after chemotherapy was 52.72 and 50.82%, respectively. The frequency of neutropenia among cancer patients was 22.32% (95% 18.26; 26.96) before chemotherapy and 27.97% (95%:23.52; 32.88) after chemotherapy, and the mean value of lymphocytes before and after chemotherapy was 37.50 and 34.29%, respectively. Lymphopenia among the study participants was 16.38% (95%:12.87; 20.62) before chemotherapy and 17.51% (95%13.88, 21.84) after chemotherapy. Among patients with stomach, rectal, and bone cancers, there was no significant difference in the counts of all blood cell types before and after chemotherapy. The mean reduction in platelets was 23. 51 × 103cells/mm3 (p = 0.001). For red blood cells (RBCs), the mean decrease was 0.63 × 106cells/mm3 (p = 0.08), and for white blood cells (WBCs), it was 2.49 × 106 cells/mm3 (p = 0.012).Conclusion and recommendationAfter chemotherapy, all hematological parameters showed a decrease, indicating that chemotherapy significant impacted the levels of these hematological parameters. Therefore, replacement therapy should be considered after chemotherapy.